THE RISE OF DIGITAL PAYMENTS: IMPLICATIONS FOR CONSUMER BEHAVIOR AND SPENDING HABITS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
The proliferation of digital payment systems has markedly reshaped consumer spending habits, influencing purchasing behavior, budgeting strategies, and overall financial planning. Driven by advancements in smartphones, internet connectivity, and fintech innovations, digital transactions— through platforms such as mobile wallets, UPI, debit/credit cards, and internet banking—are increasingly replacing traditional cash-based methods in daily life. This study investigates the impact of digital payments on consumer spending by analyzing behavioral shifts associated with the adoption of these technologies. Based on a structured survey of over 192 participants from varied demographic and economic backgrounds, the research examines patterns in digitalpayment usage, types of expenditures, perceived ease of use, and the psychological effects of cashless transactions. Employing statistical techniques, including the chi- square test, the study explores correlations between digital payment adoption and consumer expenditure trends, such as increased spending, impulsive purchases, and improved financial management through enhanced tracking and budgeting features. It also addresses user preferences and concerns regarding digital platforms, focusing on security, trust, convenience, and the role of incentives like cashbacks and promotional offers.
Keywords: Digital Payments, Consumer Spending Habits, Financial Behavior, Mobile Wallets, UPI (Unified Payments Interface), Digital Payment Adoption, Impulsive Buying, Budgeting Tools, Transaction Tracking, Chi Square Analysis.